Outbreak of tinea gladiatorum in wrestlers in Tehran (Iran) - Bassiri-Jahromi Shahindokht; Khaksar Ali (Wolters Kluwer Medknow Publications, 2008)
Background: In recent years, skin diseases in wrestling have finally received the attention they deserve. Outbreaks of tinea corporis are often associated with sports involving extensive bodily contact; such sports include wrestling. Tinea corporis gladiatorum is primarily caused by Trichophyton tonsurans , infecting wrestlers at alarming rates. The management of skin infections in wrestlers and other athletes in sports involving skin-to-skin contact entails numerous challenges, from making an accurate diagnosis to determining eligibility for playing the sports. To control outbreaks, we conducted an epidemiologic investigation. The purpose of this article is to determine the prevalence of tinea corporis gladiatorum in wrestlers in Tehran, Iran. Materials and Methods: A study of dermatophytosis was carried out during the period of March 2004 to December 2005 on 612 mycological proven cases of dermatophytosis found in male wrestlers in Tehran. Mycological examination consisted of culturing of pathologic material followed by direct microscopic observation. Diagnosis was based on macroscopic and microscopic characteristics of the colonies. Results: T. tonsurans was the predominant dermatophyte, accounting for> 90% of all tinea corporis gladiatorum isolates during the 2 year analysis. Tinea corporis gladiatorum was found to be more frequent in individuals between the ages of 10 and 20 years of age (72.7%). Wrestlers with tinea corporis gladiatorum were predominantly from wrestling clubs in southern and southeastern Tehran. Transmission of tinea corporis is primarily through skin-to-skin contact. Conclusion: Rapid identification and treatment of tinea corporis gladiatorum is required to minimize the disruption of team practices and competitions. Infection with dermatophytes can disqualify a wrestler from competing in matches, and thus, vigilant surveillance and rapid initiation of treatment is important to prevent the suspension of team practices and competitions.